Exploring the Mediating Role of Innovation in the Nexus Between National Culture and Sustainable Competitiveness - Afriyadi Cahyadi; Taufiq Marwa; Tertiarto Wahyudi; Muizzuddin; Sulastri; Ahmad Maulana; Katalin Szabó (Administrative Sciences)
This study examines the relationship between national culture, innovation, and sustainable competitiveness, addressing a critical gap in empirical research. This study engages in a rigorous investigation of the interconnections among national culture, innovation, and sustainable competitiveness, effectively addressing a significant void in the existing empirical literature. It offers a detailed and systematic analysis of the interrelationships among the three variables within the purview of an international economic framework. After conducting a comprehensive evaluation of data completeness and availability, it was determined that only 88 data points fulfilled the criteria for inclusion in the final sample. The analysis operationalizes national culture through Hofstede’s cultural dimensions, measures innovation using the World Intellectual Property Organization’s Global Innovation Index, and assesses sustainable competitiveness via Solability’s Sustainable Competitiveness Index, employing a quantitative path model across the selected countries. The findings reveal that national culture exerts a statistically significant, moderate influence on both innovation and sustainable competitiveness. Furthermore, innovation demonstrates a robust positive effect on sustainable competitiveness, indicating its crucial role in driving long-term national competitive advantage. Mediation analysis suggests that innovation partially mediates the relationship between national culture and sustainable competitiveness, though national culture retains a direct effect on competitiveness independent of innovation. These results underscore the multifaceted interplay between cultural and innovation-related factors in shaping national competitiveness. The study contributes to the literature by providing empirical validation of the complex interdependencies between these constructs and offers critical insights for policymakers focused on fostering innovation in alignment with cultural contexts to achieve sustainable competitiveness. Future research may explore additional mediating variables and employ longitudinal designs to further substantiate these findings.